The Role of Law in Creating Different Policies in Iran’s Court of Justice and Punitive Court - Mohammadi, Mohieddin; Safariani, Garnik (Cuestiones Políticas, 2020)
The principle of respecting the separation of political forces in a society gives the legal system the right to issue orders on people’s complaints based on the laws approved by the legislative power. There is no question that laws, like other man-made things, have shortcomings. These decisions include the rupture and even the conflict between two or more articles of the law that provoke the creation of different policies in the court of justice and the punitive court of Iran. With a documentary methodology, this article attempts to study the conflicts between different punitive laws and their effect on the creation of different policies in the courts of Iran. It is concluded that, in many cases, due to different reasons there may be defects in the law or in the interpretation of the law that generate defect, ambiguity, clash between laws and contradiction. The existence of all these failures in different cases will cause conflicts between the judges of the criminal courts and these conflicts are the source of the creation of different legal procedures in the criminal courts and in the short time analyzed.